2022
DOI: 10.1101/2022.09.26.509455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aminoglycoside tolerance inVibrio choleraeengages translational reprogramming associated to queuosine tRNA modification

Abstract: Tgt is the enzyme modifying the guanine (G) in tRNAs with GUN anti-codon to queuosine (Q). tgt is required for optimal growth of Vibrio cholerae in the presence of sub-lethal aminoglycoside concentrations. We further explored here the role of the Q in the efficiency of codon decoding upon tobramycin exposure. We characterized its impact on the overall bacterial proteome, and elucidated the molecular mechanisms underlying the effects of Q modification in antibiotic translational stress response. Using molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Decreased expression of these different translational modifiers might increase the rate of mistranslation and, thus, enhance tolerance toward several antibiotics ( 30 ). Notably, some recent works have shown that specific tRNA modifications could be directly involved in enhanced tolerance of aminoglycosides ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased expression of these different translational modifiers might increase the rate of mistranslation and, thus, enhance tolerance toward several antibiotics ( 30 ). Notably, some recent works have shown that specific tRNA modifications could be directly involved in enhanced tolerance of aminoglycosides ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, this study showed that the effect on fitness in the presence of sub-MIC antibiotics in tRNA modification deletion strains also impacts tolerance to lethal doses of the antibiotics. Although the molecular mechanisms underlying the effects of the queuosine Q34 modification in the antibiotic translational stress response have subsequently been described in detail [ 169 ], the mechanisms by which tRNA core modification affects antibiotic tolerance are still elusive, and their study may certainly shed new light on the subtle functions of this group of modifications.…”
Section: Trna Core Modifications and Their Impact On Translation And ...mentioning
confidence: 99%
“…Decreased expression of these different translational modifiers might be increasing the rate of mistranslation and thus enhanced tolerance towards several antibiotics (Witzky et al, 2019). Notably some recent works have shown that specific tRNA modification could be directly involved in enhanced tolerance to aminoglycosides (Babosan et al, 2022;Fruchard et al, 2022).…”
Section: Trnas Modification and Processingmentioning
confidence: 99%